THE ROLE OF DIGITAL MARKETING IN DINDA HAYU BATIK UMKM BY IMPLEMENTING 3N (NITENI, NIROKKE, NAMBAHI) - Wahyu Firmansyah, Aditya; Indah, Uliyana; Mahardikaning Sari, Puput; Alda Kaniza, Yosy; Rambu Lemba, Retno; Ayu Rahma Putri, Astrid; Ratna Purnamarini, Tri; Fauzi, Fitriya (EMPOWERING HUMANITY, 2024)
ABSTRACT The teachings of Tamansiswa 3N (Niteni, Nirokke, Nambahi) can not only be applied in the world of education. Part of the 3N concept (Niteni, Nirokke, Nambahi) can also be implemented in Dinda Hayu Batik MSMEs. This community service activity aims to examine the role of digital marketing in increasing the competitiveness of MSME Dinda Hayu Batik, a traditional batik business in Yogyakarta by implementing 3N (Niteni, Nirokke, Nambahi). The 3N approach, which means observing (niteni), imitating (nirokke), and modifying (nambahi) is used as the main strategy in optimizing digital marketing, especially on social media and e-commerce platforms. The research methods used are counseling, interviews, social media content analysis and observation. The nirokke and nambahi stages help Dinda Hayu Batik MSMEs recognize market trends and preferences, while nirokke and nambahi enable product adaptation and innovation to better suit the tastes of modern consumers without losing batik's cultural identity.